Rancangan Perangkat Lunak Computer Assisted Instruction (CAI) Untuk Ilmu Tajwid Berbasis Web - Fenny Purwani (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
The development of information technology and science refer to the need of teching-learning concept and mechanism wich are based on information technology, undoubtedly. Regarding the development, it needs qualified human resources and flexible material changing and it should be appropriate with technology and science development. Additionaly, this combines between education based on religious and techology (IMTAK and IPTEK). Internet techology can be used as teaching tool which is known as Computer Assisted Intruction (CAI). CAI software might be one of media or tool in learnig tajwid and it can help people to learn Tajwid easier.